Age-related structural and compositional variations of mouse skeletal muscle - Wang, Huijuan (2012)
Skeletal muscles undergo loss of mass and strength during aging, known as sarcopenia. Sarcopenia impairs skeletal muscle function and is characterized by a series of structural and compositional variations. In this project, I first verified that a reduced myofibre volume, i.e. atrophy, was associated with modifications in myofibre morphology. I indicated that the quantity of myonuclei (per myofibre) maintained during aging. I also reported an increased myonuclear centralization, which suggested that in the old muscle, myofibres were still capable of being regenerated by satellite cells. Although it seems well known that myonuclei yielded from a balance between their regeneration and their apoptosis, I revealed that myonuclear apoptosis was a rare event even in the old muscle. I further investigated the distribution of muscle apoptosis and noticed that most apoptosis occurred in capillary endothelial cells. Such capillary apoptosis may trigger important molecular events, i.e. cleavage of endorepellin fragments, which have been reported to stimulate fibrosis.